Managing the Rohingya Refugee Crisis in Aceh: Strategies for Conflict Management - Liska Rahayu; Suwarno, Panji; G Samudro, Eko; Widodo, Pujo; Sukendro, Achmed (Formosa Journal of Social Sciences (FJSS), 2024)
This study examines Aceh's challenges in managing Rohingya refugees and proposes conflict management strategies. Using a qualitative approach, it identifies issues in implementing Presidential Regulation 125/2016 and potential conflicts with local communities. A three-phase conflict management framework is proposed: prevention, cessation, and post-conflict recovery. Prevention strategies include developing institutional mechanisms, early warning systems, and community capacity building. Conflict cessation focuses on establishing specialized task forces and strengthening security systems. Post-conflict recovery emphasizes inclusive economic initiatives, sustained dialogue forums, integrated data management, comprehensive relocation studies, and psychosocial support. The research highlights the importance of collaborative efforts involving government agencies, international organizations, and local communities in addressing the complex challenges of refugee management